Life cycle assessment analysis of kenaf cultivation in bonorowo land, laren, lamongan - Irawati, Desrina Yusi; Wulandari, Lusi Mei Cahya (Jurnal Sistem dan Manajemen Industri, 2019)
The largest kenaf culture in Indonesia is in Laren, Lamongan. Kenaf plants are suitable to be planted in the Bonorowo field. The less potential land conditions make the cultivation of kenaf plants must use chemicals. The use of chemicals has the potential to harm the environment. The approach to identifying and analyzing environmental impacts is the Life Cycle Assessment (LCA). LCA is one method to find out the life cycle of agriculture. LCA stages are Goal and Scope Definition, Life Cycle Inventory, Life Cycle Impact Assessment, and Interpretation. Environmental impact measurement is based on fifteen categories grouped into four categories. LCA processing results show the use of urea fertilizer has the most significant negative impact on the environment. The biggest impact category due to the use of urea fertilizer is aquatic ecotoxicity. The use of urea fertilizer affects the types of resources, climate change, ecosystem quality, and human health. Of the four groups, which have the highest value, are the resource group. The use of urea fertilizer has the most significant role in the success of kenaf cultivation because kenaf cultivation requires more N elements to improve the quality of kenaf stems. The use of organic fertilizer can be an option to reduce the use of urea fertilizer.